The economic and demographic transition, mortality, and comparative development - Matteo Cervellati; Uwe Sunde (Institute for the Study of Labor (IZA), 2013)
We propose a unified growth theory to investigate the mechanics generating the economic and demographic transition, and the role of mortality differences for comparative development. The framework can replicate the quantitative patterns in historical time series data and in contemporaneous cross-country panel data, including the bi-modal distribution of the endogenous variables across countries. The results suggest that differences in extrinsic mortality might explain a substantial part of the observed differences in the timing of the take-off across countries and the worldwide density distribution of the main variables of interest.
Keywords: E10; J10; J13; N30; O10; O40; 330; economic and demographic transition; adult mortality; child mortality; quantitative analysis; unified growth model; heterogeneous human capital; comparative development; development traps